What a Women Desire: Application of Conjoint Analysis for Analysing the Choice of Menstrual Hygiene Products and Factors Influencing Their Consummatory Behaviour - Tiwari, Abhay Kumar; Patel, Vaishali; Saroj, Chitra (Scripta Medica, 2024)
Background/Aim: Middle-aged adolescent girls and women experience menstruation, a normal and physiologic occurrence. Using the myths and beliefs that were already prevalent, they created their own approach of dealing with the menstrual cycle. Aim of this study was to examine women's readiness to purchase any sanitary product by examining their preferences for the characteristics of sanitary goods used during menstruation. Methods: The utility values and relative weights assigned to various aspects, such as comfort, efficacy, hygiene, etc, have been determined through analysis. Two hundred and ten women who lived on the campus of the Banaras Hindu University were questioned. The demographic features of the respondents, the attributes with their corresponding levels and the relationship between these qualities and the type of approach employed over time are explained using descriptive and Chi-square techniques. Conjoint analysis was employed to ascertain utility value and elicit preferences. Result: Following investigation, findings indicate that synthetic sanitary napkins are used by women more frequently than any other menstrual hygiene products and that inaccessibility and cost are the main barriers to sanitary product use. Demographic factors and the type of sanitary product used, as well as knowledge of innovative methods of menstrual hygiene, were found to be strongly correlated. The results also show that women place the least value on hygiene and the most value on the type of sanitary product. Additionally, women prefer to choose any synthetic sanitary product that is more efficient, safe, pleasant and economical and does not require replacement in less than four hours.